Peran Faktor Sosiodemografi Terhadap Kemiskinan Di Provinsi Bali - Pratiwi, I Gusti Ayu Made Agung Mas Andriani; Kusmawan, I Made Hary (Universitas Tabanan, 2024)
The problem of poverty is still a problem faced by countries/regions in various parts of the world. Bali Province is one of them, especially since the Covid-19 pandemic hit and had a tremendous effect on the economy. As a province that relies on the tourism sector, the Covid-19 pandemic has hit the foundations of the economy so that statistical data shows that poverty in Bali Province tends to fluctuate and increase over the last three years. This research is focused on discussing the description of sociodemographic factors regarding poverty in Bali Province. The objectives of this research include knowing the total population, literacy rate, and per capita expenditure partially and simultaneously on poverty in Bali Province. The approach used in this research is a quantitative approach. This research uses secondary data obtained from BPS Bali Province. The data used in this research is time series data for each Regency/City in Bali Province from 2018-2022. This research uses data processing tools, namely Microsoft Excel and SPSS. The research results show that: 1) population size has a partial positive and significant effect on poverty in Bali Province; 2) literacy rates have a negative and partially insignificant effect on poverty in Bali Province; 3) per capita expenditure has a partially negative and significant effect on poverty in Bali Province; and 4) population, literacy rate, and per capita expenditure simultaneously have a positive and significant effect on poverty in Bali Province.